2023
DOI: 10.1186/s41239-022-00379-x
|View full text |Cite
|
Sign up to set email alerts
|

Learning effectiveness of a flexible learning study programme in a blended learning design: why are some courses more effective than others?

Abstract: Flexible learning addresses students’ needs for more flexibility and autonomy in shaping their learning process, and is often realised through online technologies in a blended learning design. While higher education institutions are increasingly considering replacing classroom time and offering more blended learning, current research is limited regarding its effectiveness and modifying design factors. This study analysed a flexible study programme with 133 courses in a blended learning design in different disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The collaborative and project-based learning experiences in OHSP foster creativity and critical thinking skills, and the learners frequently participate in collaborative learning activities with their peers. According to Müller et al (2023), flexible learning addresses learners' need for more flexibility and autonomy in shaping their learning process. Particular attention should be paid to the following educational design principles: adequate course structure and guidance for learners, activating learning tasks, stimulating interaction and social presence of teachers, and timely feedback on the learning process and outcomes.…”
Section: 19mentioning
confidence: 99%
“…The collaborative and project-based learning experiences in OHSP foster creativity and critical thinking skills, and the learners frequently participate in collaborative learning activities with their peers. According to Müller et al (2023), flexible learning addresses learners' need for more flexibility and autonomy in shaping their learning process. Particular attention should be paid to the following educational design principles: adequate course structure and guidance for learners, activating learning tasks, stimulating interaction and social presence of teachers, and timely feedback on the learning process and outcomes.…”
Section: 19mentioning
confidence: 99%
“…The graduates advocate for a flexible, learner-centered learning environment that incorporates alternative teaching strategies, such as ICTs, and considers their current work (Müller et al, 2023). In addition to emphasizing the benefit of adding certificates to the program outcomes to authenticate their talents and improve their resumes, they emphasize the significance of integrating theory and practice through an integrated approach to teaching and assessment (Resch & Schrittesser, 2021).…”
Section: Student Feedbacksmentioning
confidence: 99%
“…Some students have found that online learning is advantageous, which has enhanced their academic performance (Ulum, 2022). According to Müller (2023), the adaptability and simplicity of online platforms allow students to personalise their learning schedules, which may facilitate their engagement with the course material during their most productive periods (Müller, Mildenberger & Steingruber, 2023). In this regard, Fanguy (2018) also showed that the capability to rewind and review lectures enhances the understanding and review of intricate subjects (Fanguy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%